Avaliação das anormalidades do metabolismo mineral ósseo em pacientes portadores de lipodistrofia e HIV positivos - OLIVEIRA, Danielle Lima de (Universidade Federal do Pará, 2017)
The advances in antirretroviral therapy (HAART) markedly suppressed viral activity and increased longevity of those living with HIV / AIDS, however, a variety of metabolic abnormalities related to treatment was reported after the introduction of HAART combined among these complications, changes in bone mineral density arouse special attention, not only for its long-term implications, but also by the conflicting data available in the literature. OBJECTIVES: to evaluate changes in bone mineral density, and correlate them with sex, age, body mass index body, types of lipodystrophy, laboratory levels of serum calcium, parathyroid hormone and vitamin D and hormonal profile. METHODS: in this cross-sectional study 77 HIV patients with lipodystrophy syndrome treated with highly active antirretroviral therapy (HAART), and enrolled in the clinic lipodystrophy of the João de Barros Barreto University Hospital. The clinical examination of patients involved the measurement of weight, height and waist circumference. Laboratory tests performed included measurement of serum calcium, vitamin D, parathyroid hormone, estradiol, testosterone.Patients were divided into three groups according to the form of lipodystrophy: mixed, atrophic and hypertrophic. RESULTS: most patients were male, and the predominant form of lipodystrophy was mixed form. The mean time of infection after HIV diagnosis was 10.98 ± 6.03 years. The prevalence of osteopenia was 61.03% and osteoporosis was 25.97%. The male patients presented more frequently osteoporosis in femoral neck and the female patients in the lumbar spine. Osteoporosis in the lumbar spine was more prevalent in the mixed form of lipodystrophy and the femoral neck and shown to be similar between the atrophic and mixed forms of lipodystrophy. And the frequency of osteoporosis was present in all sequences of age in males and in females only after 50 years. CONCLUSIONS: the prevalence of osteoporosis increases with age in females. There was no association between BMD and the form of lipodystrophy.